Health Education and Dementia Screening In The Elderly Of Tresna Werdha Bhakti Yuswa Nursing Home South Lampung - Saftarina, Fitria; Sidharti, Liana; Mayasari, Diana; Fauzi, Ahmad; Tarigan Sibero, Hendra (Community Development Journal, 2024)
Dementia is the 4th cause of death after heart disease, cancer and stroke. To prevent dementia, 6 pillars of dementia prevention are needed. This service aims to screen for dementia and health education about preventing dementia. The benefit of this activity is to improve the quality of life for the elderly. Participatory Impact Monitoring (PIM) activity methods include involvement, active participation and community empowerment. The instrument uses the Mini Mental Status Examination (MMSE) questionnaire, sphygmomanometer, scales and microtoise. Indicators of achievement are dementia screening, health services and increasing knowledge for the elderly. The partners' targets are 34 elderly people at the Tresna Nursing Home Bakti Yuswa Natar. South Lampung. The results of the activity showed that blood pressure was hypertension stage 1 (35.29%), hypertension stage 2 (8.82%), hypertensive crisis (2.94%). Examination of nutritional status: overweight (26.47%), obesity I (8.82%), obesity II (11.76%). Dementia screening showed probable dementia (44.12%), definitive dementia (23.53%). The results of health education showed that there was a difference in the mean knowledge about dementia before and after being given health education (p=0.02). and the solutions offered are health screening, health education and the SMART Elderly program. The results disseminated are the SMART Elderly Program and health education. It requires collaboration and joint commitment from all parties to prevent dementia. The continuation of this activity is in the form of the SMART (Healthy, Independent and Active) Elderly program in collaboration with the Natar Community Health Center, South Lampung.